News Verification in the Post-Truth Era: Challenges and Behaviors of African Students in Ankara-Türkiye - Katamba Muzafalu; Brian Wandekha (Universitas Tribhuwana Tungga Dewi, 2026)
Present-day society experiences news infiltrated with diminished truth and distorted facts due to technology, resulting to consumption of hoax and fake news. As regular users of digital platforms, students are frequently exposed to fake news stories, yet their behaviors and actions for detecting, assessing, and distributing such content on social media remain unexplored. No specific research on news verification mainly targets international students in Ankara yet they depend on social media for news consumption. In this study, verification behaviors of African students in Ankara, Türkiye were examined, regarding how they classify facts and fictions in digital news about their countries. The study aims to raise awareness of news verification methods among students, expand knowledge on their news content verification, and provide insights into challenges faced in verifying digital news. With the application of mixed research methods, responses from 117 students were studied through questionnaires regarding their experiences, opinions, and knowledge on fake news verification. This research contributes original insights into the underexplored area of news verification behaviors among students, and results revealed that students still utilize social media for news consumption and using technology for verification. X emerged the most used platform for news consumption, accessibility, verification, and re-distribution with majority employing it to know news about their home countries. The study addresses a critical gap by connecting the post-truth media environment with user-driven verification practices, revealing valuable implications for media literacy strategies and digital news verification initiatives targeting student populations.